Analysis of a Mathematical Model in a Food Web System Containing Scavenger Species (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this paper, the dynamics of scavenger species  in a web food model  incorporating time delay and  prey harvesting  is formulated mathematically. Boundednes of all  solutions of the model carried out. The existence as well as stability analysis of all possible positive equilibrium points are discussed. Also, we proved that under certain time delay, our model exhibits a subcritical Hopfbifurcation. Furthermore, to confirm our analytical finding, we studied numerical simulation for the model.